Chapter 1. The Vision, Valley, and Victory of Community Engagement - Jones, Loretta (Ethn Dis, 2009)
This chapter provides an overview of Community-Partnered Participatory Research (CPPR) and introduces the articles in this special issue. CPPR is a model to engage community and academic partners equally in an initiative to benefit the community while contributing to science. This article reviews the history of the partnership of community and academic institutions that developed under the leadership of Healthy African American Families. Central to the CPPR model is a framework of community engagement that includes and mobilizes the full range of community and academic stakeholders to work collaboratively. The three stages of CPPR (Vision, Valley and Victory) are reviewed, along with the organization and purpose of the guidebook presented as articles in this issue.